Lipidic phase membrane protein serial femtosecond crystallography - Johansson, Linda; Shoeman, Robert L.; Lomb, Lukas; Epp, Sascha W.; Erk, Benjamin Michael Dieter; Foucar, Lutz Michael; Kassemeyer, Stephan; Rolles, Daniel; Rudek, Benedikt; Rudenko, Artem; Schlichting, Ilme; Ullrich, Joachim (Nature methods, 2012)
X-ray free electron laser (X-FEL)-based serial femtosecond crystallography is an emerging method with potential to rapidly advance the challenging field of membrane protein structural biology. Here we recorded interpretable diffraction data from micrometer-sized lipidic sponge phase crystals of the Blastochloris viridis photosynthetic reaction center delivered into an X-FEL beam using a sponge phase micro-jet.